KAJIAN HUKUM PIDANA TERHADAP ATAS KELALAIAN TENAGA MEDIS DI MASA COVID-19 - Siregar, Ihsan Muliadi; Zarzani, T Riza; Anwar, Yohny; Sinaga, Hary Angga; Fauzan, Fauzan (Scenario (Seminar of Social Sciences Engineering and Humaniora), 2021)
Hospitals have an obligation to provide safe, quality, and effective health services by prioritizing the interests of patients in accordance with hospital service standards. Article 46 of Law Number 44 of 2009 concerning Hospitals states that the Hospital is legally responsible for all losses caused by negligence committed by health workers at the Hospital. In carrying out medical services, doctors always try to prevent unexpected consequences or risks for patientsThe results of the writing analysis can be concluded that the hospital is responsible for negligent acts committed by medical personnel which cause harm to the patient, namely if the medical crime is committed by people who are based on work and other relationships acting in the hospital either individually or jointly. . Criminal responsibility for hospitals can be accounted for because this is the provision of Article 1367 of the Civil Code and Article 46 of the Hospital Law and juridically normative in accordance with the principle of respondeat superior, so the principle of vicarious liability, Hospital Liability, corporate liability applies, so that the hospital can be held responsible for negligence made by medical personnel who work in the position of sub-ordinate (employee), while the criminal malpractice of the medical personnel concerned must be responsible. The sanction that can be imposed is a fine with a weighting plus 1/3 (one third). The recommendation from the author is that it is necessary to make implementing regulations for the hospital's provisions which are responsible for negligence committed by medical personnel such as work relations and other relationships between the hospital and medical personnel, forms of sanctions borne by the hospital, forms of negligence committed by medical personnel and or the responsibility of medical personnel.